Social workers' perspectives : how can children and young people who have had contact with both Care and Protection and Mental Health Services be supported to experience positive outcomes? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatu, New Zealand - Mounter, Jessica (Massey University, 2018)
This thesis explored social workers’ perspectives on how children and young people who have had contact with both care and protection and mental health services can be supported to experience positive outcomes. Through thematically analysing semi-structured interviews conducted with social workers, it examined the barriers to positive outcomes and the ways in which social workers are able to utilise practice approaches which can make a positive difference in the lives of children and young people. A particular focus was given to the ways that neoliberal beliefs shaped the policy environment that governed social work practice under the Fifth National-led Coalition Government between 2008 and 2017. The thesis found that, even in this environment, social workers were able to choose to practice according to social work approaches that make a difference; particularly strength-based practice, child centred practice, focusing on family, and collaboration. The findings of this thesis imply that social workers can make a difference regardless of the policies that govern them. However, barriers and gaps in services cannot be overcome by social work practice alone and need attention from policy makers. In particular, effective intervention for complex trauma that takes into account the long developmental course that trauma related difficulties take and involves both clinical and family-based interventions needs to be prioritised by policy makers.
Keywords: Social workers; New Zealand; Interviews; Attitudes; Social work with children; Social work with teenagers; Family policy; Child welfare